2021
DOI: 10.1093/rap/rkab054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and treatment outcomes in antisynthetase syndrome: a tertiary centre experience

Abstract: Objectives The aim was to describe the clinical profile and outcomes in patients with antisynthetase syndrome (ASS) from a tertiary care centre. Methods The clinical data and investigations of all patients classified as ASS by Connors criteria over 5 years were recorded, and they were followed up prospectively. The median (interquartile range) was used for descriptive statistics. Clinical variables between the Jo-1 and non-Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Based on a targeted literature review using PubMed, previous studies utilized EIA or LIA alone for detecting anti-Ro52 antibodies and reported the prevalence of anti-Ro52 antibodies as 21.4-65.9% in patients with anti-synthetase antibodies [13][14][15][16][17][18][36][37][38][39][40][41] (Supplementary Table S1) and 31.5-74.7% in those with anti-MDA5 antibodies [13,[19][20][21][22][23][24] (Supplementary Table S2), respectively, which are compatible with the prevalence in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a targeted literature review using PubMed, previous studies utilized EIA or LIA alone for detecting anti-Ro52 antibodies and reported the prevalence of anti-Ro52 antibodies as 21.4-65.9% in patients with anti-synthetase antibodies [13][14][15][16][17][18][36][37][38][39][40][41] (Supplementary Table S1) and 31.5-74.7% in those with anti-MDA5 antibodies [13,[19][20][21][22][23][24] (Supplementary Table S2), respectively, which are compatible with the prevalence in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Table S2: Previous studies reporting the prevalence and clinical significance of anti-Ro52 antibodies in patients with anti-MDA5 antibodies. References [13][14][15][16][17][18][19][20][21][22][23][24][36][37][38][39][40][41] are cited in the Supplementary Materials. Informed Consent Statement: Informed consent was obtained from all subjects involved in the study.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…• Anti-Jo-1 (Anti-Histidyl tRNA Synthetase) Anti-Jo-1 is the most common ASAb, occurring in roughly 30-60% of ASyS patients depending on the cohort studied [47,49,73,74]. It is associated more frequently with polyarticular arthritis and muscle involvement compared to the other ASAbs [47,56,75].…”
Section: Autoantibodies Phenotypic Profilesmentioning
confidence: 99%
“…According to real-life data from the Indian MyoCite cohort (116), methotrexate (MTX) is the most employed drug, particularly in children, in whom it is prescribed as first-line treatment in 90% of cases. Azathioprine (AZA) and mycophenolate mofetil (MMF), as well as CYC and RTX, are preferred in the case of ILD and ASS (117). Anti-CD20 agents have the highest retention rate relapse-free survival (116).…”
Section: Take-home Messagesmentioning
confidence: 99%
“…Anti-CD20 agents have the highest retention rate relapse-free survival (116). In ASS, MTX is generally restricted to managing arthritis, and AZA is preferred in the case of myositis (117). Among synthetic immunosuppressants, MMF is an inactive drug hydrolysed to mycophenolic acid (MPA).…”
Section: Take-home Messagesmentioning
confidence: 99%